DIFFERENCES OF MEDICAL EUPHEMISMS IN UZBEK LANGUAGE ACCORDING TO THE SPEECH OF THE PROFESSIONAL AND AGE - Izatullayevna, Gaybullayeva Nafisa; Ahtamjonovna, Khaydarova Nodirabegim (The journal of contemporary issues in business and government, 2021)
The article discusses the development of medical euphemisms used in the speech of doctors and patients about the development of folk customs, cultural level, aesthetic taste, ethnic norms. In addition, the article focuses on the speech of different social strata and professions, typical of the speech of a medical worker - a specialist (1); medical professionals are divided into groups such as speech-specific (2) and general (3) medical euphemisms. There is also an age-related feature in Uzbek medical euphemisms.In the sense of euphemism, the sign "childhood" is based on differential signs of age; Marked "adolescent"; Marked "middle-aged"; Marked "old age"; “Age-appropriate” neutral medical euphemisms are distinguished. Hence, in the essence of medical euphemism, the specificity of social function is a linguistic unit in which the social stratum and age characteristics are generalized.